Strategic fundraising communication plan for the Office of International Programs at Colorado State University - Gerber, Anna Sprunger, author; Martey, Rosa Mikeal, advisor; Seel, Peter B., committee member; Bruyere, Brett, committee member (Colorado State University. Libraries, 2017)
As a globally-focused American institution of higher education, Colorado State University aims to bring international education opportunities to all 33,000 of its students. In 2017, CSU had more than 2,000 international students from 110 countries studying on-campus in Fort Collins. Nearly 17 percent of CSU students have an international experience – study, research, internship or service-learning opportunity abroad – before they graduate. To participate in international programs, students often incur substantial costs beyond what is required for regular class enrollment, including airfare and travel, fees, and additional tuition. These costs prevent some students from participating, and often result in higher student debt upon graduation for those who do. Additional financial resources, beyond those currently provided by the university, will allow the Office of International Programs to expand its offerings and services, increase program access to include more students, and ease the financial burden on participants. To sustain and grow CSU's international programs long-term, private funding from alumni is crucial. To facilitate fundraising that supports initiatives within the Office of International Programs and contributes to CSU's overall fundraising goals, OIP must work to solicit funds from donors through a cohesive, theory-driven fundraising communication strategy and plan for implementation. At present, communication from the university does not tap into the overwhelmingly positive experiences of CSU's education abroad alumni. This affinity group is willing to give so that future students can have international experiences, but they do not know how – more than a third do not realize that their financial support can make a difference. Using theories of fundraising success, donor motivation, and persuasive media as a foundation, this project investigated ways to engage potential donors to financially support initiatives of the Office of International Programs at Colorado State University. Research methods included informal meetings with project stakeholders, an analysis of existing data related to international student satisfaction, and the collection of an original survey that examined attitudes toward international experiences and fundraising among 499 education abroad alumni. This research determined that focusing on alumni attitudes and social norms is the most effective path to stimulate philanthropic behavior. The study found that 46% of participants think that financial contributions from people like them help make education abroad possible for CSU students, and 55% would give to the Office of International Programs if they could. Further, almost all participants had overwhelmingly positive experiences abroad, and more than 95% of them would recommend the experience to future students. These insights and others were used to develop a theory-driven, empirically-based communication plan that lays the groundwork for a successful and sustainable fundraising campaign. The plan focuses on engaging participant attitudes toward education abroad and seeks to change attitudes about giving, including social norms around giving. It proposes an approach that relies on storytelling in its communication materials to tap into alumni emotions and nostalgia. The present report provides conceptual background and previous research, an analysis of data collected for this project, and recommendations for implementation and future expansion. A separate communication plan document provides key findings and recommendations for CSU administration and staff so that they can integrate the goals and strategies of the university's overall communication, fundraising, and international strategies.